Using the politicized institutional analysis and development framework to analyze (adaptive) comanagement: farming and water resources in England - Whaley, Luke; Weatherhead, E. K. (Resilience Alliance, 2015)
The challenge of managing water resources in England is becoming increasingly complex and uncertain, a situation reflected in many countries around the world. Cooperative and participatory forms of governance are now seen as one way of addressing this challenge. We investigated this assertion by focusing on five farmer irrigator groups in the low-lying east of England. The groups’ relationship with water resources management was interpreted through the lens of comanagement, which over the past decade has increasingly merged with the field of adaptive management and related concepts that derive from resilience thinking and complex adaptive systems theory. Working within a critical realist paradigm, our analysis was guided by the politicized institutional analysis and development (IAD) framework. Two previous studies concerned with the broader context surrounding farming and water governance in lowland England revealed low levels of trust between farmers, and between farmers and water managers, as well as a power dynamic that stands in the way of farmer cooperation and participation. Within this context, our findings pointed to a number of mechanisms and structural conditions that appear to generate or facilitate comanagement. Of these, institution building through the specific group strategy of adopting a company structure and the “stationarity” of the resource group members extract from were seen to be the most crucial. These and other key findings were used to inform a discussion of farming and water resources management in England going forward. In doing so, we also reflected on the relationship between comanagement and market-based approaches to managing water resources. Beyond this, the research serves as a practical demonstration of how the politicized IAD framework can be used to analyze potential (adaptive) comanagement situations and the related benefits. The analysis complements a previous submission to this journal, in which we discussed the relationship between the framework and (adaptive) comanagement from a theoretical and methodological perspective.
Keywords: adaptive comanagement; comanagement; England; farming; politicized institutional analysis and development framework; water resources